Bladder tumors molecular aspects and clinical management - Lokeshwar, Vinata B.; Merseburger, Axel S.; Hautmann, Stefan H. (Cancer drug discovery and development., 2011)
Bladder cancer is a common cancer of the urinary tract. It is the fourth leading cause of cancer-related death among men and the seventh among women. Clinical management of bladder cancer is challenging because of the heterogeneity among bladder tumors with respect to invasion and metastasis, frequent occurrence of new tumors in the bladder among patients treated with bladder preservation treatments and poor prognosis of patients with tumors that invade the bladder muscle and beyond. Due to these factors it has been said that the cost per patient of bladder cancer, from diagnosis to death is t.